A cognitive model of persecutory delusions - Freeman, D; Garety, P; Kuipers, E; Fowler, D; Bebbington, P (2002)
A multifactorial model of the formation and maintenance of persecutory delusions is presented. Persecutory delusions are conceptualized as threat beliefs. The beliefs are hypothesized to arise from a search for meaning for internal or external experiences that are unusual, anomalous, or emotionally significant for the individual. The persecutory explanations formed reflect an interaction between psychotic processes, pre-existing beliefs and personality (particularly emotion), and the environment. It is proposed that the delusions are maintained by processes that lead to the receipt of confirmatory evidence and processes that prevent the processing of disconfirmatory evidence. Novel features of the model include the (non-defended) direct roles given to emotion in delusion formation, the detailed consideration of both the content and form of delusions, and the hypotheses concerning the associated emotional distress. The clinical and research implications of the model are outlined.